(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
The dumping of institutional, municipal, and industrial solid waste in open land creates critical challenges and problems to the geotechnical properties of soil, ecology, groundwater, and surface water. This research study outlines the impacts and influence of solid waste dumped on the chemical properties of soil. Soil samples were collected from a dumpsite at Asunle, Obafemi Awolowo University, Ile-Ife, and a control sample (200 m upstream of the dumpsite) at three different depths of 0.40 m, 0.80 m, and 1.2. m depth. Selected chemical compositions of the soils were determined using X-ray fluorescence and standard methods. Analysis of the effect of the dump site on the chemical properties of the soil was conducted using analysis of variance through Microsoft Excel functions. The study revealed that the major chemical and metallic compositions of the soil are Magnesium, Aluminium; Silicon, Phosphorus, Sulphur, Potassium, Calcium, Titanium, Vanadium, Chromium, Manganese, Iron, Cobalt, Nickel, Copper, Zinc, Tungsten, Arsenic, Gold, Lead, Rubidium, Zirconnium, Niobium, Molybdenum, Silver, Cadmium, Tin, and Antimony. The concentrations of these chemical compositions established that the materials can be grouped into four classes of concentrations of the chemicals greater than 90.0 mg/g (major-composition), between 90.0 mg/g and 25.0 mg/g (mega-composition); between 25.0 mg/g and 2.0 mg/g (micro-composition) and concentration of less than 2.0 mg/g (nano-composition). The study concluded cthat at a depth of less than 0.4m depth of the soil at the centre of the dump site, the dump site has a significant impact on the chemical composition of the soil at 95 % confidence level (F-values > F-crit) and at a depth of greater than 0.4m depth of the soil around the dump site, the dump site has no significant impact on the chemical composition of the soil at a 95 % confidence level (F-values < F-crit).